Aplicaciones aritméticas usando lógica programable - Jaquenod, Guillermo A. (2000)
Digital Signal Processing (DSP) has become a cheap, usual and standard tool, with applications in almost every area of electronics. DSP offers big advantages over classic analog processing, like high precision, bounded processing noise, etc., and in DSP algorithms addition, substraction, and multiplication are essential operators. This paper describes basic arithmetics circuits designed by using Programmable Logic Devices (CPLDs), and shows how bit-serial processing solutions can afford high computing performance with low resources usage.